2013
DOI: 10.1097/mpa.0b013e31827cddbc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Meaning of Histological Subtypes of Intraductal Papillary Mucinous Neoplasm of the Pancreas

Abstract: Although histological subtypes are associated with the degree of dysplasia, histological subtypes have limited prognostic value for pancreatic IPMNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 16 publications
3
35
1
Order By: Relevance
“…[5][6][7][8] Furthermore, studies have reported conflicting evidence on whether the histologic IPMN subtype has prognostic significance. [8][9][10][11][12] The Verona consensus meeting in 2013 recently led to the publication of guidelines for pathologic reporting of IPMN with the recommendation that pathologists provide a histologic subtype. 13 Although most previous studies used morphology and immunohistochemistry to designate the IPMN subtype, this is not necessarily implemented as standard practice.…”
mentioning
confidence: 99%
“…[5][6][7][8] Furthermore, studies have reported conflicting evidence on whether the histologic IPMN subtype has prognostic significance. [8][9][10][11][12] The Verona consensus meeting in 2013 recently led to the publication of guidelines for pathologic reporting of IPMN with the recommendation that pathologists provide a histologic subtype. 13 Although most previous studies used morphology and immunohistochemistry to designate the IPMN subtype, this is not necessarily implemented as standard practice.…”
mentioning
confidence: 99%
“…1 In a study of 283 IPMNs, Furukawa et al 6 reported a mean age of 60.3 years for 24 patients with IOPN, compared to 65.6, 64.5, and 69.2 years for gastric, intestinal, and pancreatobiliary types, respectively, and suggested an increased likelihood of earlier onset of IOPNs compared with that of the other histologic subtypes. However, other studies 9,10 have not reported a significant age difference. For example, a review by Liszka et al 10 of 24 pancreatic IOPN cases reported a mean age of 63.9 years with no significant age or sex differences between IOPN and IPMN overall.…”
Section: Clinical Featuresmentioning
confidence: 62%
“…Similarly, both cases of IOPN reported by Kang et al 9 showed high-grade dysplasia. By comparison, the study by Kang et al 9 of IPMNs in general reported 18 of 213 IPMNs with high-grade dysplasia (8.5%).…”
Section: Gross Pathologymentioning
confidence: 91%
See 2 more Smart Citations